Urgensinya Kompetensi Pedagogik dalam Pembelajaran Geografi pada Masa Pandemi Covid-19 di SMA Negeri 1 Dondo Kabupaten Toli-Toli - Suyuti; Novita, Dian (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
This study aims to determine the learning process of geography and to determine the factors supporting and inhibiting the learning process of geography during the Covid-19 pandemic at SMA Negeri 1 Dondo, Toli-Toli Regency. This research was carried out at SMA Negeri 1 Dondo located in Tinabongan Village, Dondo District, Toli-Toli Regency with a qualitative descriptive research type and used the subject of geography teachers and students. Collecting data using the method of observation, interviews, and documentation. The results showed that: 1) SMA Negeri 1 Dondo conducted Geography lessons in accordance with a circular regarding the implementation of education during the coronavirus disease (Covid19) emergency, so learning activities were carried out online. This online learning will not take long because Dondo is still in the green zone, so learning can be carried out face-to-face with an odd-even system. Learning planning at SMA Negeri 1 Dondo has held training for teachers in schools in learning design, namely making emergency lesson plans. Teachers use learning outcomes and evaluations to determine students' abilities to improve further learning. 2) Supporting factors for the Geography Learning Process during the Covid-19 Pandemic at SMA Negeri 1 Dondo are the facilities provided by the school and training held at the school for teachers. The inhibiting factor for the Geography Learning Process during the Covid-19 Pandemic at SMA Negeri 1 Dondo is that there are still teachers and students who have not mastered IT and this is considered ineffective, as well as the odd-even system that is not implemented properly.